Linked Open Data Applications, Trends and Future Developments - Okoye, Kingsley (IntechOpen, 2020)
This book intends to provide the reader with a comprehensive knowledge of the latest developments within the Linked Open Data (LOD) framework and the benefits of supported systems. The book covers the entire spectrum of "Linked Open Data - Applications, Trends and Future Developments" with six chapters. Each of the chapters provides an all-inclusive conceptualization of the LOD concepts, methodological approaches, case studies, and the main applications both in theory and practice. This book is a reference and educational book targeted to data scientists, software developers, semantic web engineers, information system designers, process managers, teachers, and researchers, and general consumers in application of LOD methods within various contexts.